Neuropsychiatric symptoms and quality of life in Spanish patients with Alzheimer’s disease during the COVID‐19 lockdown - Lara, B.; Carnes, A.; Dakterzada, F.; Benitez, I.; Piñol‐Ripoll, G. (European journal of neurology, 2020)
Background and purpose The COVID‐19 epidemic is affecting almost all individuals worldwide, and patients with Alzheimer’s disease (AD) and amnesic mild cognitive impairment (MCI) are particularly at risk due to their characteristics and age. We analysed the impact of the pandemic on these patients’ neuropsychiatric symptoms and their quality of life after 5 weeks of lockdown in Spain. Methods A total of 40 patients with a diagnosis of MCI (n = 20) or mild AD (n = 20) from the Cognitive Stimulation Program of the Cognitive Disorders Unit were evaluated. All patients had undergone a previous evaluation during the month before the lockdown, and were re‐evaluated after 5 weeks of lockdown. The Neuropsychiatric Inventory (NPI) and EuroQol‐5D questionnaire (EQ‐5D) were used to assess neuropsychiatric symptoms in patients and the quality of life in patients as well in caregivers. Results The mean (SD) total baseline NPI score was 33.75 (22.28), compared with 39.05 (27.96) after confinement (P = 0.028). The most frequently affected neuropsychiatric symptoms were apathy [4.15 (3.78) vs. 5.75 (4.02); P = 0.002] and anxiety [3.95 (3.73) vs. 5.30 (4.01); P = 0.006] in patients with MCI, and apathy [2.35 (2.70) vs. 3.75 (3.78); P = 0.036], agitation [0.45 (1.14) vs. 1.50 (2.66); P = 0.029] and aberrant motor behaviour [1.25 (2.86) vs. 2.00 (2.93); P = 0.044] in patients with AD. We did not observe differences in EQ‐5D scores during the re‐evaluation. The 30% of patients and 40% of caregivers reported a worsening of the patients' health status during confinement. Conclusions The results of this study show the worsening of neuropsychiatric symptoms in patients with AD and MCI during 5 weeks of lockdown, with agitation, apathy and aberrant motor activity being the most affected symptoms.